Policy Implementation of Solid Waste Management in South Jakarta - Siti Verawati; Retnowati Wahyuning Dyas Tuti (Universitas Medan Area, 2020)
Waste management problems are common in big cities in Indonesia, including Jakarta. Various waste problems such as: a significant increase in the volume of waste from year to year, poor waste management, and a low culture of cleanliness in the society still shackles Jakarta nowadays. The policy was initiated in the form of the DKI Jakarta Provincial Regulation No. 3 of 2013 concerning Waste Management to alleviate various solid waste problems, including through the waste bank program and 3R (Reuse, Reduce, Recycle). This study aims at analyzing the implementation of these policies using Edward III theory in Subarsono (2012) which consists of Communication, Resources, Disposition, and Bureaucratic Structure. Qualitative approaches and descriptive methods were used in this research. The results of this study are, the implementation of solid waste management policies in DKI Jakarta Selatan has not been very good. It is due to the socialization of policies and programs carried out by the government only reached the Sub-district level, not yet at the Neighbourhood level; Lack of commitment from the government and the society in supporting the implementation of good waste management. From the bureaucratic structure and authority of the Environmental Agency, it can be stated that it was quite good and met the principles of good governance, less optimal use of Â budget, with a very large budget (Rp. 3.7 trillion), the problem of flooding and waste accumulation in the river had not been resolved.